Analisis Tingkat Kebangkrutan Dengan Menggunakan Metode Altman Z-Score, Springate Dan Internal Growth Rate Pada Pt Bentoel Internasional Investama Tbk - Juhli Edi Suranta Simanjuntak; Meri Aziana; Tommy Munaf (Aksara: Jurnal Ilmu Pendidikan Nonformal, 2022)
This study aims to determine how the level of bankruptcy at PT Bentoel Internasional Investama Tbk from 2016 to 2020 using the Altmatn Z-Score, Springate, and Internal Growth Rate methods. Companies, investors and creditors are expected to consider the results of this analysis. The type of research used in this research is descriptive research, in predicting bankruptcy the researcher uses multivariate analysis. This study uses secondary data from the company's financial statements listed on the Indonesia Stock Exchange. To measure financial performance, researchers analyzed the ratios contained in the three models.The results of the analysis of the company's bankruptcy rate using the Altman Z-Score method in 2016 were the company was in the "not bankrupt" category while for 2017, 2018, 2019 the company was in the "grey area" category and in 2002 the company was categorized as "bankrupt". The results of the analysis of the bankruptcy rate as measured by the springate method show that in 2016 and 2020 the company was categorized as "bankrupt" and for 2017, 2018 and 2019 the company was categorized as "not bankrupt". For the results of measuring the bankruptcy rate using the Internal Growth Rate method in 2016, 2017, 2018 and 2019 the company was categorized as "bankrupt" and for 2020 the company was included in the "not bankrupt" category.